Body measurements of selected U.P. Diliman Filipino women students ages 16-23 - Santos, Maria Victoria Galera (College of Home Economics, University of the Philippines Diliman, 2006)
The research entitled, "Body Measurements of Selected U.P. Diliman Filipino Women Students Ages 16-23" is a descriptive study that used the survey method. The objective of this study was to determine the body measurements of selected Filipino women ages 16-23. Specifically the study aimed to measure the bust girth, waist girth and hip girth of respondents from U.P. Sampaguita Residence Hall, to come up with a body measurement chart that can be used as an updated reference for manufacturers, and to determine a size designation based on actual body measurement of selected Filipino women ages 16-23. Using a random sampling method, 113 respondents aged 16-23 were selected from the University of the Philippines Diliman, Sampaguita Residence Hall. The researcher too the bust, waist, and hip measurements of all respondents. The treatment of data utilized statistical analysis in the form of frequency distribution and data tabulation. The results showed that a body measurement chart of women ages 16-23 can be determined using actual body measurements of the selected respondents. The body measurement chart, wherein representative measurement of small, medium, large, and extra large were derived, can also be used as an updated reference for manufacturers, consumers, and retailers. Based on the body measurement chart, a size designated of small, medium, large and extra large were determined.